Survival in Metastatic Renal Cell Carcinoma Patients Treated With Sunitinib With or Without Cryoablation - Gu, Cheng-Yuan; Wang, Jun-jie; Zhang, Hai-Liang; Shi, Guo-Hai; Ye, Ding-Wei (Frontiers in Oncology, 2021)
BACKGROUND Percutaneous cryoablation (PCA) has emerged as an alternative to extirpative management of small renal masses in select patients. In recent years, the use of targeted therapies has become mainstream, while the role of PCA in treating primary tumor is not well established among patients with metastatic renal cell carcinoma (mRCC). We sought to evaluate how mRCC patients react to PCA in combination with sunitinib. METHODS We retrospectively identified patients with mRCC (primary tumor diameter ≤ 7 cm) treated with sunitinib between 2013 and 2019. These patients were categorized by initial treatment (cryoablation followed by sunitinib versus sunitinib only). Oncological outcomes and rate of adverse events were compared. RESULTS Of the 178 patients analyzed, 65 underwent PCA prior to sunitinib. The median overall survival (OS) in the PCA-sunitinib group was 31.7 months (95% CI; 26.1-37.3), better than the sunitinib-only group, which reported a median OS of 19.8 months (95% CI; 17.1-22.4) (p < 0.001). The median progression-free survival (PFS) in patients treated with PCA-sunitinib versus sunitinib alone was 13.8 months (95% CI; 10.0-17.6) versus 7.2 months (95% CI: 6.1-8.3) (p < 0.005). No significant differences in adverse events were observed (p > 0.05). CONCLUSIONS PCA combined with sunitinib is associated with better survival outcomes than sunitinib alone in patients with mRCC. Careful patient selection remains warranted. These results should inform future prospective trials.